Desain Kurikulum yang Relevan bagi Pelayanan Anak Sekolah Minggu di GKI Sumut Pealangge - Delila Damayanti Nababan (Berkat : Jurnal Pendidikan Agama dan Katolik, 2025)
The purpose of this study is to be able to design a relevant curriculum for Sunday school children at GKI Sumut Pealangge, because the Sunday school in this church does not have a curriculum and has never used a curriculum in its Sunday school children's service. The method in this study is Research and Development or what we usually call R&D (Research and Development) by following the procedures of Borg and Gall. The subjects used as research samples were Sunday school teachers at GKI Sumut in Siborongborong. The research stages include the product designer stage, the curriculum expert validation stage, the material expert or theology expert stage, and the product trial stage. The product trial stage consists of an individual trial stage with a total of 10 Sunday school teachers as trial subjects. The data analysis technique used is a qualitative and quantitative descriptive technique. The results of this design study indicate that the Sunday school children's curriculum design is considered feasible to be used as a curriculum design after passing the validation test of the curriculum expert team, and the material expert or theology expert team, as well as passing the product trial. The average score obtained as a result of the curriculum expert validation was 3.83 and 4 with the category "Good". The average score obtained as a result of validation by material experts or theologians was 4 and 4 with the category "Good". The results of individual trials obtained an average score of 27 including the category "good". The trial stage of the curriculum design product using Sunday school teachers as test subjects stated that the Sunday school curriculum design is suitable for use as a Sunday school curriculum design in supporting Sunday school children's services at GKI Sumut Pealangge.